(untitled) (Asian Journal of Medical and Biological Research, 2016)
Human Immunodeficiency virus (HIV), Hepatitis B virus (HBV), Hepatitis C virus (HCV) and Syphilis infection are the major public health problem, alarming the most developing countries like Bangladesh. These studies determined the prevalence rate and risk factors of HIV, Hepatitis B, Hepatitis C and Syphilis among nonprofessional blood donors in multiple blood transfusion center of Chittagong. Information was collected by questionnaire to find out the relationship of HIV, HBV, HCV and Syphilis infection with age, sex, socioeconomic status, residence and religious believes. The sero-prevalence of HIV, HBsAg (HBV), anti-HCV (HCV), VDRL (Syphilis) among the non-professional blood donors were 00.00%, 4.88%, 0.92%, and 0.70% respectively. So, the highest prevalence rate was HBsAg and the lowest was HIV. We didnt find more than one positive case in the same blood sample. The prevalence of HBsAg among the study population, students (120/6) were 5.00%, service holders (73/3) were 4.11%, businessmen (40/4) were 10%, housewives (14/0) were 00.00%, others (farmers, immigrant workers) (40/1) were 2.50%. The highest prevalence of HBsAg was due to illiteracy and unsafe sexual behaviors. Asian J. Med. Biol. Res. December 2015, 1(3): 518-525